Integration of P5 in Local Wisdom-Based Social Studies Learning as a Form of Strengthening the Pancasila Student Profile in Junior High Schools - Yunike Sulistyosari; Habibi Sultan; Helen Meilia (JURNAL PENDIDIKAN IPS, 2024)
Local wisdom has an important role in cultural sustainability in a global context. The current development of globalization has the potential for a shift in local values to a more attractive global culture. This research aims to determine the strategies carried out by the Taruna Nusa Harapan Junior High School, whose students have a diversity of ethnicities, religions and national origins in maintaining local wisdom values in the City of Mojokerto. This research uses qualitative methods by collecting data using in-depth interviews with P5 facilitators, teachers and students, observation and documentation. Data processing techniques use source triangulation. The results of the research show that Taruna Nusa Harapan Junior High School preserves the values of local wisdom through the Project for Strengthening the Profile of Pancasila Students (P5) by highlighting the theme of local wisdom by creating an activity entitled the Tunas Maja festival. Not only co-curricular activities, P5 Activities with the theme of local wisdom are very supportive in instilling local wisdom values in social studies learning for grades VII and VIII. The strategy used by the social studies teacher is to insert local wisdom material into relevant social studies materials such as class VII material about the relationship between the diversity of geographical conditions in the archipelago and the formation of cultural diversity. Apart from that, class VIII material, this theme is relevant to material regarding awareness of social changes that are occurring in the contemporary era with the theme of microhistory, local history, oral traditions.